THU0186 Magnitude and duration of early response with tofacitinib: post-hoc analysis of two phase 3, placebo-controlled studies. (15th June 2017) - Aletaha, D; Kivitz, A; Valenzuela, G; Tesser, J; Hays, S; Li, H; Connell, CA; Bananis, E; Soonasra, A; Smolen, JS
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of RA. ORAL Solo (NCT00814307 ) and ORAL Sync (NCT00856544 ) were two Phase 3 index studies that demonstrated the efficacy of tofacitinib in adult patients (pts) with RA who were DMARD inadequate responders (DMARD-IR). Early onset of effect is a clinically meaningful endpoint. Objectives: This post hoc analysis examined the magnitude and durability of early response to tofacitinib in ORAL Solo and ORAL Sync. Methods: ORAL Solo and ORAL Sync were double-blind, placebo (PBO)-controlled, parallel-group studies in pts with active RA and an inadequate response to ≥1 conventional synthetic (cs) or biologic (b) DMARDs. Pts were randomised to tofacitinib 5 mg BID, tofacitinib 10 mg BID, PBO advanced to tofacitinib 5 mg BID, or PBO advanced to tofacitinib 10 mg BID, either as monotherapy in ORAL Solo or with background csDMARDs in ORAL Sync. In ORAL Solo, pts randomised to PBO were advanced to tofacitinib at Month (M) 3; in ORAL Sync, pts randomised to PBO were advanced to tofacitinib at M3 (non-responders) or M6 (all other pts). In this post hoc analysis, the following clinical efficacy data for pts on tofacitinib or PBO (prior to advancement to tofacitinib) ± csDMARDs, were evaluated at Week 2, M3 and M6 (ORAL Sync only; no M6 PBO comparison in ORAL Solo): change from baseline (CFB) in Clinical Disease Activity Index (CDAI) >12, 1 HAQ-DI CFB ≥0.22, CDAI ≥50% improvement from baseline, CDAI ≥70% improvement from baseline, CDAI ≥85% improvement from baseline, Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) score improvement from baseline ≥4, Pain visual analogue scale (VAS) score CFB ≥10. This analysis was post hoc and multiplicity adjustment was done. Results: Clinical efficacy endpoint data are summarised in the Table. At Week 2, more patients receiving tofacitinib 5 or 10 mg BID ± csDMARDs (compared with PBO ± csDMARDs) achieved a CDAI CFB >12, HAQ-DI CFB ≥0.22, CDAI ≥50% improvement from baseline and pain VAS CFB ≥10. By M3, more pts receiving tofacitinib 5 or 10 mg BID ± csDMARDs (compared with PBO ± csDMARDs) achieved the efficacy outcomes measured including improvements from baseline in FACIT-F scores ≥4, CDAI ≥50%, CDAI ≥70% and CDAI ≥85%. Responses attained at M3 were maintained or increased at M6. Conclusions: DMARD-IR pts with active RA receiving tofacitinib ± csDMARDs appeared to show greater improvements compared with PBO in clinical disease activity, HAQ-DI, and pain as early as Week 2 (first post-baseline assessment), and improvements in fatigue by M3. Responses were maintained or improved through M3 (monotherapy) or M6 (with background csDMARDs). References: Curtis JR et al. Arthritis Care Res (Hoboken) 2015; 67:1345–1353. Acknowledgements: Previously presented at ACR 2016 and reproduced with permission. This study was sponsored by Pfizer Inc. Editorial support was provided by AG McCluskey of CMC and was funded by Pfizer Inc. Disclosure of Interest: D. Aletaha Consultant for: AbbVie, BMS, Eli Lilly, Janssen, MSD, Pfizer Inc, Roche, and UCB, Speakers bureau: AbbVie, BMS, Eli Lilly, Janssen, MSD, Pfizer Inc, Roche, and UCB, A. Kivitz Grant/research support from: AbbVie, Amgen, Bristol Myers Squibb, Genentech, Pfizer Inc, Consultant for: AbbVie, Amgen, Bristol Myers Squibb, Genentech, Pfizer Inc, Speakers bureau: AbbVie, Amgen, Bristol Myers Squibb, Genentech, Pfizer Inc, G. Valenzuela Speakers bureau: AbbVie, Janssen, Eli-Lilly, Merck, Novartis and Pfizer Inc, J. Tesser Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, S. Hays Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, H. Li Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. A. Connell Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Bananis Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Soonasra Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. S. Smolen Grant/research support from: AbbVie, Janssen, Lilly, MSD, Pfizer Inc, and Roche, Consultant for: AbbVie, Amgen, AstraZeneca, Astro, Celgene, Celtrion, Glaxo, ILTOO, Janssen, Lilly, MedImmune, MSD, Novartis-Sandoz, Pfizer Inc, Roche, Samsung, Sanofi, and UCB, Speakers bureau: AbbVie, Amgen, AstraZeneca, Astro, Celgene, Celtrion, Glaxo, ILTOO, Janssen, Lilly, MedImmune, MSD, Novartis-Sandoz, Pfizer Inc, Roche, Samsung, Sanofi, and UCB